2021
DOI: 10.32598/jspi.9.4.9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cognitive-metacognitive Strategies Training and Positive Psychology Training on Academic Self-efficacy, Academic Burnout, and Learning Strategies

Abstract: Objective: The present research aimed to explore the effects of cognitive-metacognitive strategies and positive psychology training skills on academic self-efficacy, academic burnout, and learning strategies. Methods: This was a quasi-experimental with an unequal control group design. The statistical population included students in Arak City, Iran, in the academic year 2019-2020. Accordingly, 45 of whom were selected using the convenience sampling method and randomly divided into 3 experimental and control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Fredericks et al (2004) reported a reliability coefficient of 0.86. Abbasi et al (2015) obtained the reliability of this questionnaire using Cronbach’s alpha of .66. The present study’s reliability coefficient based on Cronbach’s alpha index was .78.…”
Section: Methodsmentioning
confidence: 99%
“…Fredericks et al (2004) reported a reliability coefficient of 0.86. Abbasi et al (2015) obtained the reliability of this questionnaire using Cronbach’s alpha of .66. The present study’s reliability coefficient based on Cronbach’s alpha index was .78.…”
Section: Methodsmentioning
confidence: 99%